The effect of diet and phytotherapy in the treatment of acne vulgaris - Agnieszka Dorota Kaźmierska; Izabela Bolesławska; Juliusz Przysławski (Polish Pharmaceutical Society, 2020)
Summary The aim of the dissertation was to determine the impact of diet and medicinal plants in the treatment of acne vulgaris. The effect that can be achieved by implementing herbal raw materials in therapy is primarily a reduction in sebum production and the creation of new skin inflammations. It has been shown that plants are very helpful in the treatment of acne vulgaris. Awareness of the significant impact of diet can contribute to reducing the scale of the problem associated with the occurrence of acne vulgaris. The occurrence of acne vulgaris is widely recognised as a common phenomenon affecting almost 100% of the population (Langner, 2000). It is estimated that 80% of youths are affected by this disease, which may contribute to stress and depression (Braun-Falco, 2004). Numerous studies concerning the influence of nutrients on health indicate that a proper diet determines the body's health responses. The findings of this paper clearly show a relationship between consumed products and the condition of acneous skin. The interest in the impact of diet and nutrients on the skin that has been observed in recent years has led to the development of the field of dietetics and phytotherapy. This direction of development, however, is not well understood. It is worth conducting research to determine the influence of diet and phytotherapy on the condition of human skin and health. Phytotherapy should be a supplement to conventional treatment. The methods of our ancestors worked well when there were no synthetic drugs (Ożarowski, 1990). Skin diseases are a major therapeutic problem. The use of plant substances brings great hopes for modern medicine, cosmetology, dietetics, and pharmacy. The medicinal substances of plant origin have a wide spectrum of anti-inflammatory, analgesic, and regulating hormone activity (Ożarowski, 1990). Herbal medicines can be used for both treatment and prevention. They exhibit a slower and milder effect, and also do not cause microbial resistance, which is often manifested when using antibiotic therapy (Ożarowski, 1990). We are currently observing a return to naturotherapy. In many cases, medicinal plants can slow down the symptoms of a disease when other methods do not bring the desired results.